(untitled) (Editora Impacto Científico, 2025)
The present work objectifies to evaluate the soils of an area of 40,5 ha. placed in the Municipal district of Afonso Bezerra-RN, for agricultural ends through the determination of pH of the soil and of the saturated extract of the soil; of the indexes of exchangeable and soluble cátions and, starting from these, to esteem the affectation degree through capacity of exchange of cátions (CTC), exchangeable sodium percentage (ESP) and reason of adsorção of sodium (SAR), existent in them alluviums placed partly of Rio Cabugí’s Basin, in the Municipal district of Afonso Bezerra-RN. Besides those properties chemistries they are appraised the following physical properties: speed of infiltration of the water in the soil, the granulometria (percentages of sand, silte and clay) and electric condutividade of the saturated extract of the soil (CEES). The evaluation of these properties was made through analyses in laboratory of soil samples collected in four layers, in the depths of 0-30 cm, 31-60 cm, 61-90 cm and 91-150 cm. DOI: https://doi.org/10.56238/edimpacto2025.090-045